Natural Killer Cell-Derived Extracellular Vesicles: Novel Players in Cancer Immunotherapy - Wu, Feifeng; Xie, Min; Hun, Marady; She, Zhou; Li, Cuifang; Luo, Senlin; Chen, Xiaoyu; Wan, Wuqing; Wen, Chuan; Tian, Jidong (Frontiers in Immunology, 2021)
Natural killer (NK) cells are critical components of host innate immunity and function as the first line of defense against tumors and viral infection. There is increasing evidence that extracellular vesicles (EVs) are involved in the antitumor activity of NK cells. NK cell-derived EVs (NKEVs) carrying cargo such as cytotoxic proteins, microRNAs, and cytokines employ multiple mechanisms to kill tumor cells, but also exhibit immunomodulatory activity by stimulating other immune cells. Several studies have reported that NKEVs can reverse immune suppression under tolerogenic conditions and contribute to NK-mediated immune surveillance against tumors. Thus, NKEVs are a promising tool for cancer immunotherapy. In this review, we describe the biological effects and potential applications of NKEVs in antitumor immunity.